Analisis Narasi Propaganda Kelompok Radikal di Media Sosial: Studi Diskursus Khilafatul Muslimin di Facebook (2019-2024) [Analysis of Radical Group Propaganda Narratives on Social Media: Disourse Study of Khilafatul Muslimin on Facebook (2019-2024)] - Ulum, Muhammad Rafisqi; Damayanti, Angel (Jurnal Politica, 2025)
Social media serves as a significant platform for radical groups to disseminate propaganda narratives that strengthens group support and fosters loyalty among existing members. The spread of radical ideas that contradict Pancasila and the 1945 Constitution poses a threat to the integrity of the Unitary State of the Republic of Indonesia (NKRI). Therefore, this paper aims to analyze the narratives propagated by the Khilafatul Muslimin group through Facebook from 2019 to 2024. This study examined the narrative discourse, focusing on how the group conveyed their messages, the content of their propaganda, and the public's responses to the material they posted. The research employed a qualitative methodology, incorporating website-based sentiment analysis and discourse analysis. The researchers applied concepts of propaganda and counter-propaganda, as well as discourse and narrative analysis, supplemented by triangulation of data gathered from interviews with key informants, including spokespersons of the Khilafatul Muslimin group, experts on radicalism, and policymakers. The findings indicate that the Khilafatul Muslimin's discourse on Facebook is characterized as grey propaganda, primarily relying on narratives with religious themes and socio-political implications. Consequently, counter-propaganda initiatives need to be implemented by the government, involving religious leaders and influencers to effectively counter the opposing arguments presented in these narratives.AbstrakMedia sosial menjadi platform penting bagi kelompok radikal untuk menyebarluaskan narasi propaganda karena dapat membangun pemahaman yang mendukung kelompok tersebut serta memastikan loyalitas anggota yang ada. Penyebaran paham radikal yang bertentangan dengan Pancasila dan UUD 1945 mengancam keutuhan Negara Kesatuan Republik Indonesia (NKRI). Itu sebabnya, tulisan ini bertujuan untuk menganalisis narasi yang disebarluaskan oleh kelompok Khilafatul Muslimin melalui facebook sepanjang tahun 2019-2024. Peneltiian ini menganalisa diskursus narasi yang dibangun oleh kelompok Khilafatul Muslimin, termasuk cara mereka menyampaikan pesan, isi pesan propaganda dan bagaimana publik merespon konten yang mereka unggah. Penelitian ini menggunakan metodologi kualitatif dalam bentuk analisis sentimen berbasis website dan analisis wacana. Para peneliti memanfaatkan konsep propaganda dan kontra-propganda serta diskursus dan narasi, yang dilengkapi dengan triangulasi data yang berasal dari wawancara dengan narasumber yang terdiri dari juru bicara kelompok Khilafatul Muslimin, pakar radikalisme dan pembuat kebijakan. Hasil penelitian menunjukkan bahwa penyebaran diskursus Khilafatul Muslimin di facebook merupakan propaganda abu-abu dan paling banyak menggunakan narasi bertema religius dan sosial politik. Hal ini dapat dilihat dari lima kata yang paling sering muncul dalam unggahan dan diskusi mereka. Itu sebabnya, pemerintah perlu melakukan kontra-propaganda dengan melibatkan tokoh-tokoh agama dan influencer untuk mematahkan argumentasi negatif dari narasi-narasi tersebut.